Determinan Foreign Direct Investment (FDI) di Negara-negara Organisasi Kerjasama Islam (OKI) Periode 2010-2019 - Mahendra, Weri (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2021)
This study explains how the influence of GDP, exports, HDI, corruption perception index and democracy index on Foreign Direct Investment (FDI) in 15 OIC countries, namely Kazakhstan, Saudi Arabia, Indonesia, Turkey, Malaysia, United Arab Emirates, Azerbaijan, Egypt, Nigeria, Lebanon, Morocco, Tunisia, Bangladesh, Pakistan, Albania in 2010-2019. The existence of Foreign Direct Investment in a country can be useful as state revenue from tax sources, as well as the relationship between technology transfer, transfer of management expertise, development of entrepreneurial output and increasing the rate of national income in the economy. This study uses quantitative methods with secondary data and data collection through the World Bank, Transparency International, United Nations Development Program (UNDP) and The Economist Intelligence Unit. This study also uses panel data regression with the best model approach, namely the Random Effect Model (REM), to determine how much influence the independent variables such as GDP, exports, HDI, corruption perception index and democracy index have on the dependent variable (FDI). Based on the results of the F test obtained, it shows that in general the five independent variables have a positive and significant effect on FDI. Meanwhile, the T test results show that the GDP and export variables have a positive and significant effect on FDI. In the HDI variable, the corruption perception index and the democracy index have no effect on FDI. [Penelitian ini menjelaskan bagaimana pengaruh PDB, ekspor, IPM, indeks persepsi korupsi dan indeks demokrasi terhadap Foreign Direct Investment (FDI) di 15 negara OKI yaitu Kazakhstan, Arab Saudi, Indonesia, Turki, Malaysia, Uni Emirat Arab, Azerbaijan, Mesir, Nigeria, Libanon, Moroko, Tunisia, Bangladesh, Pakistan, Albania pada tahun 2010-2019. Adanya Foreign Direct Investment dalam suatu negara dapat bermanfaat sebagai penerimaan negara dari sumber pajak, serta adanya hubungan alih teknologi, transfer keahlian manajemen, perkembangan wirausaha output serta menaikkan laju pendapatan nasional dalam perekonomian. Penelitian ini menggunakan metode kuantitatif dengan data sekunder dan pengambilan data melalui World Bank, Transparency International, United Nations Development Programme (UNDP) dan The Economist Intelligence Unit. Penelitian ini juga menggunakan regresi data panel dengan pendekatan model terbaik yaitu Random Effect Model (REM), untuk mengetahui seberapa besar pengaruh variabel bebas seperti PDB, ekspor, IPM, indeks persepsi korupsi dan indeks demokrasi terhadap variabel terikat (FDI). Berdasarkan hasil uji F yang diperoleh, menunjukkan bahwa secara umum kelima variabel bebas berpengaruh positif dan signifikan terhadap FDI. Sedangkan pada hasil uji T menunjukkan bahwa variabel GDP dan ekspor berpengaruh positif dan signifikan terhadap FDI. Pada variabel HDI, indeks persepsi korupsi dan indeks demokrasi tidak memiliki pengaruh terhadap FDI.]